Analisis Implementasi Pembelajaran SKI Berbasis Game Kahoot dalam Mengatasi Kejenuhan Belajar Siswa di MAN 3 Nganjuk - Nia Zuliyanti; Ummiy Fauziyah Laili; Mochamad Desta Pradana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the teaching of Islamic Cultural History (SKI) in Islamic Senior High Schools, which frequently encounters issues of school burnout, particularly when the instructional process still relies heavily on oral delivery and conventional presentations. This condition results in a lack of focus, learning motivation, and active student engagement throughout the teaching and learning activities. Based on preliminary observations and interviews conducted at MAN 3 Nganjuk, it was found that eleventh-grade students exhibited relatively high levels of school burnout in the SKI subject. Therefore, this study aims to analyze the implementation of Kahoot-based game learning in SKI to overcome students’ school burnout, as well as to examine the factors that facilitate and hinder the implementation of this learning activity at MAN 3 Nganjuk. This study employed a qualitative approach with a descriptive research design. The research subjects included the SKI subject teacher, the vice principal for curriculum affairs, and students of classes XI-1 and XI-2 at MAN 3 Nganjuk. Data were collected through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation to confirm the trustworthiness of the research findings. The research findings indicate that: (1) The implementation of game-based SKI learning using Kahoot at MAN 3 Nganjuk was carried out properly and systematically. The learning process began with the opening session, followed by group presentations, a question-and-answer session, reinforcement of the material, and continued with the implementation of Kahoot using team mode, concluding with closing activities and the distribution of rewards. (2) The use of Kahoot has proven to be effective in reducing students’ school burnout, increasing their participation, focus, and learning motivation in SKI classes. Learning through team mode creates a more active and engaging classroom environment while encouraging positive competition. In addition, there was an improvement in students’ understanding of the material, as reflected in their involvement in discussions and their learning evaluation results. (3) The supporting factors for the implementation of Kahoot include the availability of facilities and infrastructure, students’ technological literacy, teachers’ competence, technical readiness and collaborative culture, platform flexibility, as well as effective learning management and motivation. Meanwhile, the inhibiting factors include unstable internet connections, device and infrastructure constraints, technical limitations of the platform, time constraints, and the pedagogical preferences of some teachers.